Understanding proxy decision‐makers' perspectives of frailty and frailty tools to support decision‐making for persons with dementia. (1st February 2022) - Shapkin, KImberly; Bent, Haley; Callaway, Lorna; Cooper, Mary Elizabeth; Randhawa, Sukhjeet Kaur; Murphy, Angela; Lazar, Faye; Cuthbert, Colleen
Abstract: Background: Proxy decision‐makers' for persons with dementia (PwD) have identified feeling uninformed about the prognosis and progression of dementia and unsupported by healthcare professionals. One aim of our study was to explore how frailty is understood and if frailty tools may assist with decision‐making. Method: We conducted a qualitative inquiry using focus groups to explore decision‐makers understanding of frailty and their perspectives of using frailty tools. Proxy decision‐makers were identified as formal agents of a PwD. Focus groups were recorded and transcribed verbatim. Data was analyzed and interpreted using thematic analysis. Result: Analysis revealed the prevailing theme to be, frailty is understood as a mosaic . Decision‐makers' primarily consider frailty a physical phenomenon, closely paralleling Fried's (2000) frailty phenotype: weight loss, low activity, slow gait, weakness and fatigue. Participants also associated frailty with cognitive decline and emotional instability. Applying the term frailty to PwD produced an ambivalent response in participants, although the term itself was considered as acceptable to describe physical decline. Participants valued the Clinical Frailty Scale to aid in the understanding of the progression of physical decline, but felt the limited recognition of cognitive decline was a barrier. The fluctuating course of dementia also limited the utility of using a tool with fixed categories. Conclusion: Frailty is a recognizable term to proxy decision‐makers, but is understood in a variety of ways, primarily as a physical phenomenon. Given the ambivalence in using this term and decision‐makers' focus on cognitive changes, discussing frailty has little to add to improve supporting decision‐making in dementia.